MENINGKATKAN KETERAMPILAN PROSES SAINS MELALUI PEMBELAJARAN KOLOID DENGAN LEMBAR KERJA PRAKTIKUM BERORIENTASI CHEMO-ENTREPRENEURSHIP - Sumarti, Sri Susilogati; Nuswowati, Murbangun; Kurniawati, Eti (Phenomenon : Jurnal Pendidikan MIPA, 2018)
The skill of the scientific process is the ability that are used to perform scientific investigations. This study aims to determine chemo-entrepreneurship (CEP) oriented student worksheet can improve science process skills.  The research method used is quantitative by using test results and observation. The samples in this study were the students of class XI IPA SMA Negeri 9 Semarang. The data shows that the average score is 80.1% of students are in the minimum criteria score in the process and the results are good predicate. The indicator of observing skills gets the highest score on the results of observations with an average score of 3.90. The skill of hypothesesis gets the lowest average score with an average score of 2.84. Based on the results of the test, the indicators of the skill to apply the concept get the highest average score of 9.48 and the skill level in planning experiment gets the lowest average score with a score of 8.5.Based on the results of the study, it can be concluded that the CEP-oriented student worksheetcan improve their science proccess skills.